The effects of live streamer’s expertise and entertainment on the viewers’ purchase and follow intentions - Jiang, Yaping; Lee, Hyoung-Tark; Li, Wei (Frontiers in Psychology, 2024)
This study explores the impact of two characteristics of streamers—expertise and entertainment—on viewers’ purchase intention and follow intention in live-streaming e-commerce, with a specific focus on viewers’ trust and flow experience as two mediators and viewers’ optimal stimulation level as a moderator. We implemented a methodological approach where participants were randomly directed to enter a live broadcast room and watch a 10-min live session before engaging in a structured questionnaire. 399 valid questionnaires were collected from the participants. These 399 valid questionnaires were subsequently utilized to validate the research model using structural equation modeling (SEM). The results suggest that streamer expertise and entertainment enhance viewers’ trust and flow experience, which then leads to an increase in their intention to make a purchase and continue following the streamer. Furthermore, the viewers’ optimal stimulation level acts as a moderator in the connections between streamer characteristics and viewers’ trust and flow experience, suggesting that individual differences among consumers affect how they respond to streamer characteristics. From the dual perspectives of the streamer and the viewer, this study provides a more comprehensive theoretical perspective on customer behavior in live streaming commerce by not only focusing on consumers’ short-term, transactional behavior inclinations but also long-term, relational behavior intentions.